Recent trends in trade union membership in Ireland - Walsh, Frank; Strobl, Eric (Economic & Social Studies, 2009)
Using micro data from the Quarterly National Household Survey we look at trends in Irish union membership from 2001-2006. There was a steep decline in union density. Decomposition analysis suggests that most of the decline is associated with a decline in the underlying probability of becoming a member for different groups of workers rather than a change in composition.
Paper delivered at the Twenty-Second Annual Conference of the Irish Economic Association, Westport, Co. Mayo, 25-27 April, 2008
Keywords: Trade unions; Membership; Ireland; Labour force